Study on the vee-block refractometer - Campitelli, Enrique J. (1980)
The vee block (Hilger-Chance) refractometer is to be preferred jn the optical shop because of its good precision, because it measures the bulk and not the skin refractive index, and for the little work needed in the preparation of the sample. The latter is its most important feature. (Párrafo extraído a modo de resumen)